1990
DOI: 10.1007/bf00404794
|View full text |Cite
|
Sign up to set email alerts
|

Experimental diabetes impairs rat embryo development during the preimplantation period

Abstract: Congenital malformations and early fetal losses are still the main complications of diabetic pregnancy. Whether the diabetic state affects the early embryo development during the preimplantation period is not known. To understand better the early steps of embryo growth, we collected the embryonic structures from the uterine horns of pregnant diabetic rats on day 5 of pregnancy. Diabetes was induced by streptozotocin (50 mg/kg) injection, 7, 14 or 21 days before mating. The morphological analysis revealed a low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0
2

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 35 publications
3
45
0
2
Order By: Relevance
“…On day 5 of pregnancy, diabetic rats were tested for their blood glucose concentration and those with a glycaemia above 11 mmol/1 were ether anaesthetized. Preimplantation embryos were collected from the uterine horns and immediately transferred onto an inverted phase-contrast microscope [7].…”
Section: Collection Of Preimplantation Embryosmentioning
confidence: 99%
See 2 more Smart Citations
“…On day 5 of pregnancy, diabetic rats were tested for their blood glucose concentration and those with a glycaemia above 11 mmol/1 were ether anaesthetized. Preimplantation embryos were collected from the uterine horns and immediately transferred onto an inverted phase-contrast microscope [7].…”
Section: Collection Of Preimplantation Embryosmentioning
confidence: 99%
“…Interesting data pertaining to this issue have been obtained in experiments showing that preimplantation embryos from either drug-treated or spontaneous diabetic mice have a decreased ability to develop in vitro when maintained under the same culture conditions as control embryos [5,6]. These observations were made at the morphological level, however, and it is not known whether such a discrepancy in growth potential extends to more subtle differences in the rate of embryonic cell proliferation and differentiation.In a previous study on the impact of the maternal diabetic condition on preimplantation growth in vivo, we demonstrated that blastocysts collected from diabetic rats contained fewer cells than control embryos [7] and that cells from the lineage responsible for forming the fetus were more affected in their proliferation than the cell population that gives rise to the placenta [8]. This deficiency in preimplantation development was corrected by treating the dia-…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dans le but de comprendre le rôle du métabolisme lipidique dans l'étiopathologie de la macrosomie, nous avons développé dans notre laboratoire un modèle animal. Il a été démontré que l'administration de streptozotocine (STZ), avant la grossesse, affecte la fertilité et altère le développement de l'embryon pendant la période de pré-implantation (Vercheval et al, 1990). Pour cette raison, dans notre modèle, nous avons injecté, à des rattes Wistar femelles, par voie intrapéritonéale, une dose unique de 40 mg/kg de poids corporel de STZ, au 5 e jour de la gestation et n'avons observé aucun effet délétère sur le développement de l'embryon.…”
Section: Le Métabolisme Des Lipides Et Des Lipoprotéines Est Altéré Cunclassified
“…Altered oocyte maturation, ↓ blastocysts, total, TE and ICM number ↑ Morulae ↓ Outgrowth of P-TGC at 72h culture (Diamond et al, 1989, Lea et al, 1996, Moley et al, 1991, Pampfer et al, 1994, Vercheval et al, 1990) High Fat Diet, mouse, in vivo, -16 weeks -E0 or E4, in vitro to E5 ↓ Oocyte quality, ICM and blastocyst number, ↑ TE cells ↑ Igf2R expression (Jungheim et al, 2010, Minge et al, 2008 Ethanol, mouse, in vitro, oocytes, 1-, 2-or 4-cell embryos exposed to 0-2% (w/v) EtOH on one day, cultured to blastocyst stage.…”
Section: Models Of Periconceptional Programmingmentioning
confidence: 99%